Pronunciation Patterns and Challenges of the Japanese Long Vowel (Chouon) /ei/ Among Indonesian Students - Febriyanti, Rike (Chi e Journal of Japanese Learning and Teaching, 2024)
This study examines the pronunciation patterns of the Japanese vowel sequence /ei/ among 62 students from six universities across six provinces in Indonesia. In Japanese, the vowel sequence /ei/ is commonly neutralized to /e:/. According to Takayama (1992), this neutralization is incomplete in formal or careful speech, where /ei/ is pronounced distinctly as /ei/. Hashimoto (2006) observed that speakers alternate between /ei/ and /e:/, particularly at the ends of sentences. This research explores how Indonesian students, who typically pronounce words according to their written forms, produce the vowel sequence /ei/ in both the initial and final positions of familiar Japanese words. This study was conducted between January to June 2024. Participants were tasked with identifying instances where native Japanese speakers used the long vowel /ei/ in sentences. They then recorded their pronunciations of these words in various positions. The recordings were analyzed using PRAAT software. Results show that native Japanese speakers typically pronounce /ei/ as a long /e:/ with an average duration of 0.173 seconds. In comparison, Indonesian learners pronounced /ei/ in "reizouko" with an average duration of 0.204 seconds and in "yotei" with 0.148 seconds, indicating a tendency for longer pronunciation at the beginning of words. The longest recorded duration was 0.49 seconds, and the shortest was 0.04 seconds, possibly due to hesitation. Furthermore, learners tended to simplify the /ei/ sound, especially at the start or end of sentences. This study highlights the need for targeted pronunciation instruction and additional practice time in Japanese language curricula to address these specific phonetic challenges.